2013
DOI: 10.1177/1545968313510974
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Therapy Provides a Stimulus for Upper Limb Motor Recovery After Stroke That Is Complementary to and Distinct From Conventional Therapy

Abstract: Data suggest that robotic therapy can elicit improvements in arm function that are distinct from conventional therapy and supplements conventional methods to improve outcomes. Results from this pilot study should be confirmed in a larger study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 41 publications
4
33
0
1
Order By: Relevance
“…Reduced compliance and engagement with the home-based intervention could have been a factor for these individuals. Additionally, the potential for gains may have already been exhausted in these 2 subjects; they were the only subjects in the group who participated in a prior treatment study that involved 24 hours of upper extremity therapy, 12 of which involved using the HandSOME in conjunction with an arm robot [38]. A larger sample size could provide additional information about the characteristics of the individuals most likely to benefit from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced compliance and engagement with the home-based intervention could have been a factor for these individuals. Additionally, the potential for gains may have already been exhausted in these 2 subjects; they were the only subjects in the group who participated in a prior treatment study that involved 24 hours of upper extremity therapy, 12 of which involved using the HandSOME in conjunction with an arm robot [38]. A larger sample size could provide additional information about the characteristics of the individuals most likely to benefit from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy provided assistance as correction to bad motion coordination of the main joints active during the task, in particular on shoulder and elbow joints. This controller was tested on 12 impaired subjects in a 3-month pilot study [96]. Data suggested that this robotic therapy could elicit improvements in arm function that were distinct from conventional therapy (improved inter-joint coordination), and thus it could integrate to conventional methods to improve outcomes.…”
Section: B Corrective Modesmentioning
confidence: 99%
“…Pilot studies establishing the feasibility of these systems describe clinical outcomes comparable or superior to those reported in studies of traditionally presented rehabilitation. 1114 A newer study by Klamroth-Marganska et al compared an integrated upper extremity robotic intervention to a dose-matched program of RTP. 15 They identified a small impairment level advantage for the virtually simulated/robotic training condition, but activity level changes were identical for the two groups.…”
Section: Introductionmentioning
confidence: 99%